Efficacy and safety of temelimab in multiple sclerosis: Results of a randomized phase 2b and extension study. (March 2022) - Hartung, Hans-Peter; Derfuss, Tobias; Cree, Bruce AC; Sormani, Maria Pia; Selmaj, Krzysztof; Stutters, Jonathan; Prados, Ferran; MacManus, David; Schneble, Hans-Martin; Lambert, Estelle; Porchet, Hervé; Glanzman, Robert; et al.
Background: The envelope protein of human endogenous retrovirus W (HERV-W-Env) is expressed by macrophages and microglia, mediating axonal damage in chronic active MS lesions. Objective and Methods: This phase 2, double-blind, 48-week trial in relapsing-remitting MS with 48-week extension phase assessed the efficacy and safety of temelimab; a monoclonal antibody neutralizing HERV-W-Env. The primary endpoint was the reduction of cumulative gadolinium-enhancing T1-lesions in brain magnetic resonance imaging (MRI) scans at week 24. Additional endpoints included numbers of T2 and T1-hypointense lesions, magnetization transfer ratio, and brain atrophy. In total, 270 participants were randomized to receive monthly intravenous temelimab (6, 12, or 18 mg/kg) or placebo for 24 weeks; at week 24 placebo-treated participants were re-randomized to treatment groups. Results: The primary endpoint was not met. At week 48, participants treated with 18 mg/kg temelimab had fewer new T1-hypointense lesions ( p = 0.014) and showed consistent, however statistically non-significant, reductions in brain atrophy and magnetization transfer ratio decrease, as compared with the placebo/comparator group. These latter two trends were sustained over 96 weeks. No safety issues emerged. Conclusion: Temelimab failed to show an effect on features of acute inflammation but demonstrated preliminary radiological signs of possible anti-neurodegenerative effects. Current data support the development of temelimab for progressive MS. Trial registration: CHANGE-MS: ClinicalTrials.gov: NCT02782858, EudraCT: 2015-004059-29; ANGEL-MS: ClinicalTrials.gov: NCT03239860, EudraCT: 2016-004935-18